1998
DOI: 10.1080/00332747.1998.11024831
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Adoption: Long-Term Effects in Adulthood

Abstract: Clinicians and researchers have characterized early life experiences as permanent and stable influences on the personality and subsequent life experiences of an individual. Recent conceptualizations have suggested that personal and environmental factors influencing development are not deterministic. Multiple pathways into adulthood are possible. Adoption is one potential early life stressor that may illustrate the usefulness of such conceptualizations for assessing long-term effects in adulthood. Previous stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 30 publications
1
25
1
Order By: Relevance
“…Most studied adjustment in childhood or adolescence, but some looked at adults-mostly under age 30. There have been a few recent studies of adoptees at later ages, including a British study (Collishaw et al 1998) that assessed adoptee adjustment at age 33, and a Swedish study (Smyer et al 1998) that involved 60 pairs of older twins (mean age 56), one of whom had been adopted away and one reared by the biological parent. Wierzbicki's meta-analysis of adoption outcome studies concluded that: (1) adoptees have more adjustment problems than biological children in similar families, although fewer than a birth mother's other children kept and reared by her; (2) the problems are predominantly of an externalizing kind (truancy, fighting, lying, stealing, substance abuse, and the like);…”
Section: Life Outcomesmentioning
confidence: 98%
“…Most studied adjustment in childhood or adolescence, but some looked at adults-mostly under age 30. There have been a few recent studies of adoptees at later ages, including a British study (Collishaw et al 1998) that assessed adoptee adjustment at age 33, and a Swedish study (Smyer et al 1998) that involved 60 pairs of older twins (mean age 56), one of whom had been adopted away and one reared by the biological parent. Wierzbicki's meta-analysis of adoption outcome studies concluded that: (1) adoptees have more adjustment problems than biological children in similar families, although fewer than a birth mother's other children kept and reared by her; (2) the problems are predominantly of an externalizing kind (truancy, fighting, lying, stealing, substance abuse, and the like);…”
Section: Life Outcomesmentioning
confidence: 98%
“…Some studies compared adopted and non-adopted young adults, mainly focusing on mental health and psychological well-being; however, results of these studies are not consistent and have exhibited contradictory findings. On one hand, a number of studies demonstrated that adult adoptees are more likely to be at higher risk for psychopathological outcomes and lower level of psychological well-being (Cubito & Obremski Brandon, 2000;Cantor-Grace & Pedersen, 2007;Feeney, Passmore, & Peterson, 2007;Hjern, von Borczyskowski, Lindblad, & Vinnerljung, 2006;Levy-Shiff, 2001;Passmore, Fogarty, Bourke, & Baker-Evans, 2005;Tieman, van der Ende, & Verhulst, 2005), while other studies failed to find any differences in adjustment and in psychological wellbeing between adopted and non-adopted adults (Borders, Penny, & Portnoy, 2000;Feigelman, 2000;Irhammar & Bengtsson, 2004;Kelly, Towner-Thyrum, Rigby, & Martin, 1998;Smyer, Gatz, Simi, & Pedersen, 1998).…”
mentioning
confidence: 97%
“…In a recent article, my colleagues and I have argued that adoption research can usefully be placed within two theoretical frameworks: stress and coping literature and life-span developmental psychology (Smyer, Gatz, Simi, & Pedersen, 1998). In each case, we are trying to place the topic of adoption within bigger theoretical boxes to improve our understanding of both adoption and the larger theories.…”
Section: Adoption: the Bigger Boxesmentioning
confidence: 98%